Vacuum Rabi Splitting and Strong-Coupling Dynamics for Surface-Plasmon Polaritons and Rhodamine 6G Molecules - Hakala, T. K.; Toppari, J. J.; Kuzyk, A.; Pettersson, M.; Tikkanen, H.; Kunttu, H.; Törmä, P. (Physical review letters, 2009)
We report on strong coupling between surface-plasmon polaritons (SPP) and Rhodamine 6G (R6G) molecules, with double vacuum Rabi splitting energies up to 230 and 110 meV. In addition, we demonstrate the emission of all three energy branches of the strongly coupled SPP-exciton hybrid system, revealing features of system dynamics that are not visible in conventional reflectometry. Finally, in analogy to tunable-Q microcavities, we show that the Rabi splitting can be controlled by adjusting the interaction time between waveguided SPPs and R6G deposited on top of the waveguide. The interaction time can be controlled with sub-fs precision by adjusting the length of the R6G area with standard lithography methods.